Solve for x 0.08-0.01(x+1)=-0.02(4-x)

Math
0.08-0.01(x+1)=-0.02(4-x)
Simplify 0.08-0.01(x+1).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
0.08-0.01x-0.01⋅1=-0.02(4-x)
Multiply -0.01 by 1.
0.08-0.01x-0.01=-0.02(4-x)
0.08-0.01x-0.01=-0.02(4-x)
Subtract 0.01 from 0.08.
-0.01x+0.07=-0.02(4-x)
-0.01x+0.07=-0.02(4-x)
Simplify -0.02(4-x).
Tap for more steps…
Apply the distributive property.
-0.01x+0.07=-0.02⋅4-0.02(-x)
Multiply.
Tap for more steps…
Multiply -0.02 by 4.
-0.01x+0.07=-0.08-0.02(-x)
Multiply -1 by -0.02.
-0.01x+0.07=-0.08+0.02x
-0.01x+0.07=-0.08+0.02x
-0.01x+0.07=-0.08+0.02x
Move all terms containing x to the left side of the equation.
Tap for more steps…
Subtract 0.02x from both sides of the equation.
-0.01x+0.07-0.02x=-0.08
Subtract 0.02x from -0.01x.
-0.03x+0.07=-0.08
-0.03x+0.07=-0.08
Move all terms not containing x to the right side of the equation.
Tap for more steps…
Subtract 0.07 from both sides of the equation.
-0.03x=-0.08-0.07
Subtract 0.07 from -0.08.
-0.03x=-0.15
-0.03x=-0.15
Divide each term by -0.03 and simplify.
Tap for more steps…
Divide each term in -0.03x=-0.15 by -0.03.
-0.03x-0.03=-0.15-0.03
Cancel the common factor of -0.03.
x=-0.15-0.03
Divide -0.15 by -0.03.
x=5
x=5
Solve for x 0.08-0.01(x+1)=-0.02(4-x)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top